2.Uporządkuj jednomiany:
a) y · 6 x =
b) –5b ·7ba ·(-2)=
c) x·(-6)x ·y =
d) 2 x · 3 x2 =
e) 12cd·0,2 c2 · d3 =
f) (-x)·(-a)·12a·(-0,3 x2 )=
3.Przedstaw w jak najprostszej postaci:
a) 16x-5y-6-21x+19y-8=
b) -(9a-b+7) + (6+a- 8b) =
c) 5(x-3y) – 4(x-2) + (y-1)=
d) 2x (4,1xy – 0,5y+3,2x) – (5x2 – 3,4xy+1,2x2 y) ·3=
e) (3x – 5) – (2x + 4)=
f) 4(3x – 5) – 3(2x + 4)=
g) (7x – 3) – 4(2x + 4) + 7x =
h) 5(a - b)- 7a (a - b)=


Prosze o odpowiedzi xD

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-21T21:01:42+01:00
2.
a) y · 6 x = 6xy
b) –5b ·7ba ·(-2)= 70ab²
c) x·(-6)x ·y = -6x²y
d) 2 x · 3 x2 = 6x³
e) 12cd·0,2 c2 · d3 = 2,4c³d^4 (do potęgi 4)
f) (-x)·(-a)·12a·(-0,3 x2 )= -3,6a²x³
3.Przedstaw w jak najprostszej postaci:
a) 16x-5y-6-21x+19y-8= -5x+14y-14
b) -(9a-b+7) + (6+a- 8b) = -9a+b-7+6+a-8b = -8a-7b-1
c) 5(x-3y) – 4(x-2) + (y-1)= 5x-15y-4x+8+y-1 = x-14y+7
d) 2x (4,1xy – 0,5y+3,2x) – (5x2 – 3,4xy+1,2x2 y) ·3=
8,2x²y-xy+6,4x²-15x²+10,2xy-3,6x²y =
9,2xy+4,6x²y-8,6x²
e) (3x – 5) – (2x + 4)= 3x-5-2x-4 = x-9
f) 4(3x – 5) – 3(2x + 4)= 12x-20-6x-12 = 6x-32
g) (7x – 3) – 4(2x + 4) + 7x =7x-3-8x-16+7x = 6x-19
h) 5(a - b)- 7a (a - b)= 5a-5b-7a²+7ab
2010-03-21T21:02:25+01:00
2.Uporządkuj jednomiany:
a) y · 6 x =6xy
b) –5b ·7ba ·(-2)=70ab²
c) x·(-6)x ·y =-6x²y
d) 2 x · 3 x2 =6x³
e) 12cd·0,2 c2 · d3 =2,4c³d⁴
f) (-x)·(-a)·12a·(-0,3 x2 )=-3,6a²x³
3.Przedstaw w jak najprostszej postaci:
a) 16x-5y-6-21x+19y-8=-5x+14y-14
b) -(9a-b+7) + (6+a- 8b) =-9a+b-7+6+a-8b=-8a-7b-1
c) 5(x-3y) – 4(x-2) + (y-1)=5x-15y-4x+8+y-1=x-14y+7
d) 2x (4,1xy – 0,5y+3,2x) – (5x2 – 3,4xy+1,2x2 y) ·3=8,2x²y-xy+6,4x²-15x²+10,2xy-3,6x²y=4,6x²y+9,2xy-8,6x²
e) (3x – 5) – (2x + 4)=3x-5-2x-4=x-9
f) 4(3x – 5) – 3(2x + 4)=12x-20-6x-12=6x-32
g) (7x – 3) – 4(2x + 4) + 7x =7x-3-8x-16+7x=6x-19
h) 5(a - b)- 7a (a - b)=5a-5b-7a²+7ab
1 5 1